A new porphyrin as selective substrate-based inhibitor of breast cancer resistance protein (BCRP/ABCG2). (5th January 2022) - Zattoni, Ingrid Fatima; Kronenberger, Thales; Kita, Diogo Henrique; Guanaes, Lais Danciguer; Guimarães, Matheus Murmel; de Oliveira Prado, Larissa; Ziasch, Melanie; Vesga, Luis C.; Gomes de Moraes Rego, Fabiane; Picheth, Geraldo; Gonçalves, Marcos Brown; Noseda, Miguel D.; et al.
Abstract: The ABCG2 transporter plays a pivotal role in multidrug resistance, however, no clinical trial using specific ABCG2 inhibitors have been successful. Although ABC transporters actively extrude a wide variety of substrates, photodynamic therapeutic agents with porphyrinic scaffolds are exclusively transported by ABCG2. In this work, we describe for the first time a porphyrin derivative (4B ) inhibitor of ABCG2 and capable to overcome multidrug resistance in vitro . The inhibition was time-dependent and 4B was not itself transported by ABCG2. Independently of the substrate, the porphyrin 4B showed an IC50 value of 1.6 μM and a mixed type of inhibition. This compound inhibited the ATPase activity and increased the binding of the conformational-sensitive antibody 5D3. A thermostability assay confirmed allosteric protein changes triggered by the porphyrin. Long-timescale molecular dynamics simulations revealed a different behavior between the ABCG2 porphyrinic substrate pheophorbide a and the porphyrin 4B. Pheophorbide a was able to bind in three different protein sites but 4B showed one binding conformation with a strong ionic interaction with GLU446. The inhibition was selective toward ABCG2, since no inhibition was observed for P-glycoprotein and MRP1. Finally, this compound successfully chemosensitized cells that overexpress ABCG2. These findings reinforce that substrates may be a privileged source of chemical scaffolds for identification of new inhibitors of multidrug resistance-linked ABC transporters. Graphical abstract: Image 1 Highlights: New porphyrin (4B) described as selective non transported ABCG2 inhibitor. The inhibition occurs in substrate-independent manner. 4B enhances recognition of conformational antibody 5D3 with mild ATPase inhibition. 4B showed one single conformation on MD with a strong interaction with Glu446. 4B successfully reverted the resistance phenotype in vitro .